(untitled) (Global Journal of Human-Social Science, 2015)
This paper investigates comparative study of 2011 and 2015 presidential elections in Nigeria with specific focus on the Fourth Republic, from the comparative analysis perspectives. Thus, through the use of comparative theory unfolds the causes responsible for the opposition travail in the 2015 election in Nigeria. By the use of the comparative analysis we try to know what is common and find out the causes and consequences for the victory and the losses. This research also presents statistical data analysis of the both elections, for comparison. It was undertaking to ascertain the nature and character of the 2011 and 2015 election. This article therefore recommends that in order for the electoral system to be free and fair, there is need for government to place priority on education through free and compulsory education, Avoid inflammatory rhetoric, publicly denounce violence, pledge to respect rules, in particular the Code of Conduct for Political Parties, and pursue grievances through lawful channels, it also indicate that the sovereign power belongs to the people. The era of political parties taking people for granted is gone. Nigerians are very conscious of their rights; they know with their votes is they can install or remove government that failed to perform.